Use of Ultrasound to Investigate Glucose Oxidase and Storage Effects on the Rheological Properties of Cooked Asian Noodles. Issue 2 (23rd November 2015) - Daugelaite, Daiva; Strybulevych, Anatoliy; Scanlon, Martin G.; Page, John H.; Hatcher, David W.
Abstract : This is the first use of a longitudinal ultrasonic technique to address the rheological properties of cooked noodles. Ultrasound (11 MHz) was utilized to investigate the influence of glucose oxidase (GOx) at the 1.5 U/g of flour level on the rheological properties of cooked alkaline noodles before and after 72 h of storage at 4°C. Cooked noodle dough samples were studied by simultaneously conducting stress relaxation and transmission ultrasonic measurements, yielding Peleg's K1 and K2 parameters (initial rate of relaxation and extent of relaxation, respectively) and ultrasonic information on noodle texture properties. Ultrasonic phase velocities and attenuation coefficients did not show significant differences between control and GOx noodles either before or after 72 h of refrigeration. However, refrigerated storage of control and GOx noodles did result in a significant increase in wave velocity and storage modulus ( M′ ) as well as a decrease in attenuation and tan δ L (ratio of longitudinal loss modulus to longitudinal storage modulus), indicating increased firmness of noodle structure with storage time. Stress relaxation results on fresh unrefrigerated noodles showed an increase in Peleg's K1 and K2 parameters with GOx addition but did not resolve any significant changes in these parameters after 72 h of storage. This small amount of GOx did not improve cooked noodle texture, although noodle matrix changes during storage were clearly revealed by the noninvasive ultrasonic data.